A female focus great women photographers - Horwitz, Margot F (New York F. Watts, 1996)
Surveys the work of American women photographers over the past 150 years, examining what they photographed and why, as well as how they worked.
Keywords: Women photographers -- United States -- History -- Juvenile literature; Photography -- United States -- History -- Juvenile literature; Photographers; Photography -- History; Women -- Biography